Performance Evaluation of Solar-Powered Hydrothermal Equipment for Rice Husk Biomass Treatment - Martunis; Adi Setiawan; Abubakar Dabet; Jumadi Rusli; Riza Andriani; Gunawati (Institute for Research and Community Service (LPPM), Universitas Malikussaleh, Indonesia, 2026)
This study aims to analyze the performance of a solar-powered hydrothermal reactor with a capacity of 1 liter, utilizing a parabolic solar collector in the heating process of rice husk. The use of solar energy as an alternative heat source is expected to reduce dependence on fossil fuels and support the development of environmentally friendly technologies. This research employs an experimental method with a quantitative analysis approach. Two variations of raw material mixing ratios were tested: a 1:1 ratio (1 kg of water: 1 kg of rice husk) and a 1:2 ratio (500 grams of rice husk: 1 kg of water). Each ratio was tested three times, monitoring parameters such as material temperature, pressure, ambient temperature, and solar light intensity over a period of 3 hours. The results indicate that the hydrothermal device can achieve a maximum temperature of up to 135°C and a maximum pressure of 36 psi. The highest average temperature was obtained at the 1:1 ratio, measuring 95.46°C, while the 1:2 ratio yielded 85.80°C, demonstrating a significant difference in heating effectiveness. The effectiveness of the solar collector is highly dependent on solar light intensity and weather conditions. This study concludes that the parabolic solar collector is effective as a heat source in small-scale hydrothermal systems and has great potential for application in the processing of biomass waste based on renewable energy in tropical regions.